2021
DOI: 10.1186/s11782-021-00103-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dark tetrad personality traits on nascent entrepreneurial behavior: the mediating role of entrepreneurial intention

Abstract: The impact of negative personality traits on entrepreneurial intention and entrepreneurial behavior has become a research focus in the field of entrepreneurship. This study aimed to identify the influence of dark tetrad personality traits on the nascent entrepreneurial behavior and the mediating role of entrepreneurial intention. This study used partial least square-structural equation modeling (PLS-SEM) to test the hypotheses on a sample of 347 undergraduate and postgraduate university students from China. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 68 publications
5
41
1
2
Order By: Relevance
“…This study provides four main contributions to literature on entrepreneurship. First, existing studies have been focused on entrepreneurial traits such as family business (Douglas et al, 2021), big five personality traits (Bazkiaei et al, 2020), the dark side of personality traits (Cai et al, 2021), entrepreneurial self-efficacy (Ceresia and Mendola, 2020), and entrepreneurial alertness (Urban, 2020) to determine the entrepreneurial intention of the student. Second, Wardana et al (2020) argued that there is a lack of study into an entrepreneurial education and entrepreneurial mindset on entrepreneurial intention; most of the previous studies have been investigated on entrepreneurship education and entrepreneurial mindset in the context of Europe (Boldureanu et al, 2020), America (Barnard et al, 2019), Africa (Puni et al, 2018), Malaysia (Shamsudin et al, 2017), and India (Jena, 2020), while little attention has been paid by scholars to the context of China.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides four main contributions to literature on entrepreneurship. First, existing studies have been focused on entrepreneurial traits such as family business (Douglas et al, 2021), big five personality traits (Bazkiaei et al, 2020), the dark side of personality traits (Cai et al, 2021), entrepreneurial self-efficacy (Ceresia and Mendola, 2020), and entrepreneurial alertness (Urban, 2020) to determine the entrepreneurial intention of the student. Second, Wardana et al (2020) argued that there is a lack of study into an entrepreneurial education and entrepreneurial mindset on entrepreneurial intention; most of the previous studies have been investigated on entrepreneurship education and entrepreneurial mindset in the context of Europe (Boldureanu et al, 2020), America (Barnard et al, 2019), Africa (Puni et al, 2018), Malaysia (Shamsudin et al, 2017), and India (Jena, 2020), while little attention has been paid by scholars to the context of China.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, entrepreneurship programs should be considered basic courses for business undergraduates, thanks to which students are trained to have moral and appropriate attitudes, critical skills, and information (Chen, Greene, & Crick, 1998). Furthermore, self-regulation and social responsibility should be developed to reduce the harmful effects of dark characteristics on humanity and business (Cai et al, 2021;Hmieleski & Lerner, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, psychopaths have a strong desire for self-promotion and impression by status, dominance, prestige, and nance, which might be well demonstrated in an entrepreneurial career. Therefore, previous articles indicated that a high level of psychopathy within individuals positively correlates with start-up intention (Cai et al, 2021;Kramer et al, 2011).…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations